Potensi Dua Macam Pestisida Nabati dengan Perekat Lidah Buaya Untuk Menekan Kerusakan Hama Daun Tanaman Sawi (Brassica juncea L.) - Separnawa, Muhammad Nur; Pramudi, Muhammad Indar; Soedijo, Samharinto (www.ulm.ac.id, 2025)
This research aims to determine the potential of the botanical pesticide papaya leaves and neem leaves treated with aloe vera leaf adhesive and without aloe vera leaf adhesive in controlling leaf pests on mustard greens in the Unlam Faculty of Agriculture Experimental Garden. The design used in this research was a one-factor Completely Randomized Design (CRD) with 5 treatments and 4 replications. Each experimental unit consisted of 4 polybags with 2 mustard plants planted in each polybag. Overall in this study there were 160 mustard plants, treatments consisted of K = Control (water), P1 = Papaya leaf solution + aloe vera leaves, P2 = Neem leaf solution + aloe vera leaves, P3 = Papaya leaf solution without aloe vera leaves, P4 = Neem leaf solution. The results of this study showed that all Botanical pesticide treatments sprayed on mustard greens showed no difference, namely P1 = (42.33%), P2 = (38.82%), P3 = (37.53%), P4 = (36.92%). However, it is significantly different from the control, 47.69%. The lowest leaf pest attack was seen in the neem leaf (P4) 34.92%.